Abandon Policies for Two Types of Multiattempt Missions - Yuejiao Feng (Journal of Mathematics)
Systems that perform critical missions will often be affected by internal degradation until they reach a failure state. For safety critical systems that perform certain tasks, failure of the systems will have serious consequences. In such scenarios, the survival of the systems has a higher priority than the completion of the task. The task can be suspended at an appropriate time and a rescue procedure can be initiated to reduce the risk of system failures. When the task is important, the systems can try to execute the task multiple times after the task is abandoned and the rescue is completed, to improve the probability of task completion. This study further expands the existing research on multiple task abandon strategy by proposing degradation-based multicriteria mission abandon policies considering multiattempts and two types of task success criteria. The task is abandoned dynamically based on the degradation level and time in the mission in each attempt. Under the dynamic abandon policies, mission reliability, and systems survivability are evaluated using the recursive method. The optimal abandon thresholds are investigated numerically.